If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 5) = 22 Reorder the terms: 2(5 + x) = 22 (5 * 2 + x * 2) = 22 (10 + 2x) = 22 Solving 10 + 2x = 22 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 2x = 22 + -10 Combine like terms: 10 + -10 = 0 0 + 2x = 22 + -10 2x = 22 + -10 Combine like terms: 22 + -10 = 12 2x = 12 Divide each side by '2'. x = 6 Simplifying x = 6
| 4a-a+3a=0 | | -4x+9x-3=-13 | | 6x-3y-5x+3y= | | 5x-a=2ax+7 | | 16-10x=21-2x | | 3x^2-5x+5=0 | | 6x+5=7x+16 | | 12m=7 | | n+31=51 | | 16-5s=31 | | n+10=15 | | 5m+74=34 | | 13-2v=7 | | .66-3y=5.66 | | 16+1.25x=10 | | -2x+y=10 | | 6.2x+2=5.2x-4 | | 2.5y=36 | | 2.5y=37 | | 7x+21=4x+102 | | 88-7x=38x-23 | | 4x+12=9x+13 | | 130-8x=9x+23 | | 14x=84+7x | | -7x-10=7x-122 | | 5(2x-8-2)=5(x-3)+3 | | -a+7b-ab+4ab-b+1= | | 11x+5-3=10x-2 | | 120-2x=6x+24 | | 9x^3-36x^2-4x+16= | | 9x^3-36x^2-4x+16=0 | | (-9)(-32)= |